Two novel species of Sisyranthus (Apocynaceae—Ceropegieae) from South Africa - Shabangu, Khanyisile; Bester, Stoffel P.; van Der Bank, Michelle (Phytotaxa, 2020)
Sisyranthus species are cryptic in both their habit and small size of their flowers making them difficult to find in the wild. The genus was last revised in Flora Capensis (1908) and since then, two new species have been described. Currently it comprises 13 recognised species endemic to southern Africa. Many of these are range-restricted and poorly known. In this contribution the genus is further expanded by describing two novel species. Full descriptions, assessment of conservation status, distribution maps and line drawings of the new taxa are presented.